2017
DOI: 10.1039/c7ra07083g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flame-retardancy and controlled physical properties of flexible polyurethane foams based on a shear-responsive internal network

Abstract: The flame retardancy of FPUFs can be enhanced by the manipulation of the solid-polymer interface chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In the case when solid additives are used, they need to be dispersed well for uniform functional properties [21]. It has been demonstrated that a proper dispersion of additives in the polyol is necessary for long-term storage stability of bridged DOPO polyol dispersions [22]. Thus in an attempt to improve the flame retardancy of EDA-DOPO in formulations B, pre-dispersion of EDA-DOPO in polyol using a planetary ball mill was performed.…”
Section: Resultsmentioning
confidence: 99%
“…In the case when solid additives are used, they need to be dispersed well for uniform functional properties [21]. It has been demonstrated that a proper dispersion of additives in the polyol is necessary for long-term storage stability of bridged DOPO polyol dispersions [22]. Thus in an attempt to improve the flame retardancy of EDA-DOPO in formulations B, pre-dispersion of EDA-DOPO in polyol using a planetary ball mill was performed.…”
Section: Resultsmentioning
confidence: 99%
“…König et al 24,25 synthesized new phosphorus ame-retardant methyl-DOPO in a exible polyurethane foam and then contributed to the gas-phase activity of ame inhibition. Gaan et al 26 and Rao et al 27 synthesized DOPO-based phosphonamidate additives and incorporated them in the polyurethane manufacturing process. The above-mentioned studies indicate that DOPO phosphonamidates exhibit better ame-retardant efficiency than the commercial ame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…The figure’s legend denotes the experiment’s timing, which runs from 0 (i.e., the beginning state of suspension) to the final position of suspension at 179 s of centrifugation. There is frequently a linear correlation between settling velocity and RCF [ 43 , 53 ], which lends credence to the idea that the particles are monodisperse and that Stokes’ equation may be utilized to analyze the samples. Overall, it appears that the shape and porosity of the particles may have a significant impact on the settling velocity of the particles [ 43 , 53 ], as will be demonstrated.…”
Section: Resultsmentioning
confidence: 99%